The TORCH time-of-flight detector for Upgrade II of the LHCb experiment - Blake, T; Cicala, F; Conneely, T; Cussans, D; Davidson, A; Frei, C; Forty, R; Gao, R; Gershon, T; Gys, T; Hadavizadeh, T; Hancock, T; et al. (Elsevier, 2024)
The TORCH (Time Of internally Reflected Cherenkov light) detector is proposed for the high-luminosity Upgrade II of the LHCb experiment. The aim of TORCH is to measure time-of-flight with a 15 ps resolution per charged-particle, providing particle identification over the momentum range 2–15 GeV/c. TORCH is to be located approximately 9.5 m downstream of the LHCb interaction point, and comprises 18 modules of highly-polished 1 cm-thick quartz plates, each of 250×66cm2. Cherenkov photons, radiated in the quartz, are focused onto an array of fast-timing micro-channel-plate detectors (MCP-PMTs) that each have a pixelation of 8 × 64 within an active area of 5.3 × 5.3 cm2. Test-beam studies have previously shown that a timing resolution better than 100 ps per single photon can be achieved on a half-height module. Recent advances in the development of a 16 × 96 pixelated MCP-PMT are described. A full-height module is being developed with a light-weight carbon-fibre support structure. A novel exo-skeleton jigging system is used to bond the optical elements and support each module during installation.